2013
DOI: 10.1021/nn404840h
|View full text |Cite
|
Sign up to set email alerts
|

Templated Self-Assembly and Local Doping of Molecules on Epitaxial Hexagonal Boron Nitride

Abstract: Using low-temperature scanning tunneling microscopy, we show that monolayer hexagonal boron nitride (h-BN) on Ir(111) acts as ultrathin insulating layer for organic molecules, while simultaneously templating their self-assembly. Tunneling spectroscopy experiments on cobalt phthalocyanine (CoPC) reveal narrow molecular resonances and indicate that the charge state of CoPC is periodically modulated by the h-BN moiré superstructure. Molecules in the second layer show site-selective adsorption behavior, allowing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
147
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 96 publications
(162 citation statements)
references
References 49 publications
15
147
0
Order By: Relevance
“…This gives rise to a fundamental difference in the electronic properties: While Gr is a zero-band-gap semiconductor, h-BN is an excellent insulator with a bandgap of about 5 eV [1]. Because of its inertness, flatness, structural perfection, and insulating character, cleaved bulk hexagonal boron nitride or monolayers of h-BN are now widely used as substrates for organic molecules [2,3], topological insulators [4], and graphene [5]. Hexagonal boron nitride is established as a key component in vertical van der Waals heterostructures [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…This gives rise to a fundamental difference in the electronic properties: While Gr is a zero-band-gap semiconductor, h-BN is an excellent insulator with a bandgap of about 5 eV [1]. Because of its inertness, flatness, structural perfection, and insulating character, cleaved bulk hexagonal boron nitride or monolayers of h-BN are now widely used as substrates for organic molecules [2,3], topological insulators [4], and graphene [5]. Hexagonal boron nitride is established as a key component in vertical van der Waals heterostructures [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Another area of interest in h-BN are the so-called boron nitride nanomeshesepitaxial monolayers of h-BN grown on transition metal surfaces [4,5]. Various studies have been motivated by their ability to act as a template for bottom-up fabrication techniques, while simultaneously providing electronic decoupling from the metallic substrate [4,[6][7][8][9][10][11][12][13]. The term "nanomesh" highlights the peculiar structure of the h-BN monolayers: Due to the lattice mismatch with the underlying substrate, the atomic registry between the boron and nitrogen atoms and the metallic surface is periodically modulated, resulting in a moiré pattern formed by regions of stronger h-BN/metal and weaker h-BN/metal interaction.…”
Section: Introductionmentioning
confidence: 99%
“…This feature, which can also be discerned in Figure 1a, closely resembles the highest occupied π molecular orbital (π-HOMO) level of a Pc ligand as seen in DFT calculations of an isolated molecule. [19] STM images of weakly interacting Pc molecules on thin insulators [14,34] and the decoupled top Pc ligand of a double decker Pc molecule [35][36][37] also exhibit this same electronic structure.…”
mentioning
confidence: 74%
“…[11,12] For example, it has been shown that molecules can become trapped within nanopores of hexagonal boron nitride grown on Ru (0001) because of dipolar interactions; [13,14] similar results have also been observed for nanopores on the surface of bulk SiC. [15] Physisorption of a molecule to a surface (i.e., van der Waals bonding) is often not strong enough to fix the molecule's position at room temperature, particularly on the surface of bulk metal crystals.…”
mentioning
confidence: 99%